Theory of surface cyclotron X-modes at the second harmonic of electron cyclotron frequency excited by alternating electric field - Girka, A.V.; Girka, V.O.; Pavlenko, I.V. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
Instability of surface cyclotron X-modes at the second harmonic of electron cyclotron frequency (SCXM) in di-electric planar waveguide filled by plasma is studied in kinetic approximation. An external magnetic field is assumed parallel to the plasma surface. Doing that, two components of the SCXM wave vector, which are perpendicular to external magnetic filed have been taken into the account in Vlasov-Boltzmann kinetic equation. Unlike the previous consideration an amplitude value of the alternating electric field is assumed to be either less or approximately equal to unit. Simple expressions for growth rates of the SCXM parametrical instability are calculated. The obtained results can be used for controlling of gas discharges sustained by surface waves under the regime of electron cyclotron resonance.